Assessing risk factors and causative organisms of acute diarrhea in children under 5 years in AL-Hindiya, Karbala, Iraq - Haider Sahib Humady Tuky; Ban Abbas Semender (Medical Journal of Babylon, 2019)
Background: Acute diarrhea is a leading source of illness and death all over the world, especially in developing countries and the most affected are children below 5 years age. Objectives: To throw a light on the risk factors, presentations, and causative organisms of acute diarrhea, to find a way to protect our children. Materials and Methods: This prospective cross-sectional study was conducted on 250 children under 5 years of age; they attended AL-Hindiya general Hospital, in the period between November 2018 and end of June 2019. Full history was taken from each patient focused on risk factors, presentation, and possible complications; then, patients were subjected to clinical examination, stool analysis, and stool culture, and some of them were sent for abdominal ultrasound. Results: The most vulnerable age group for acute diarrhea was 2–12 months. Male to female ratio is 1.17. Crowded family and poor income were the most frequently risk factors to develop acute diarrhea. Bottle feeding was used in 111 patients (44.4%); improper sewage and trash disposal, poor hand washing practice, incomplete vaccination, prior use of antibiotics, and underweight all are considerable risk factors. The peak for acute diarrhea occurs during summer (63.6%). Those patients most commonly presented as watery bowel motion less than or equal to five times per day, well-hydrated, vomiting, fever, associated with upper respiratory tract infection. There is no growth of organism in stool sample of 126 patients (50.4%), while Entamoeba histolytica isolated from 34 samples (13.6%). Conclusion: Children under 5 years in A-Hindiya city still at considerable risk of acute diarrhea. The risk is more in rural, young, low educated, unemployed, and poor parents with crowded families. It is vital to encourage breastfeeding, immunization, improve personal hygiene, water supply, and sanitation to reduce the risks of acute diarrhea. The most frequent isolated organism from stool samples is E. histolytica followed by Rota virus.